Outcome after hip arthroscopy for femoroacetabular impingement in 289 patients with minimum 2‐year follow‐up. (21st January 2016) - Sansone, M.; Ahldén, M.; Jónasson, P.; Thomeé, C.; Swärd, L.; Öhlin, A.; Baranto, A.; Karlsson, J.; Thomeé, R.
Abstract : Femoroacetabular impingement (FAI) is a common cause of hip pain and dysfunction. The purpose of this study was to report outcome 2 years after the arthroscopic treatment of FAI using validated outcome measurements. Two hundred and eighty‐nine patients (males = 190, females = 99) with a mean age of 37 years underwent arthroscopic surgery for FAI. Patients were included consecutively in a hip arthroscopy registry. The cohort was evaluated using online web‐based validated health‐related patient‐reported outcomes measurements, including the iHOT‐12, HAGOS, EQ‐5D, HSAS for physical activity level, VAS for overall hip function and overall satisfaction. The mean follow‐up time was 25.4 months. Pre‐operative scores compared with those obtained at follow‐up revealed statistically and clinically significant improvements ( P < 0.05) for all measured outcomes; iHOT‐12 (43 vs 66), VAS for global hip function (50 vs 71), HSAS (2.9 vs 3.6), EQ‐5D index (0.58 vs 0.75), EQ‐VAS (67 vs 75) and HAGOS different subscales (56 vs 76, 51 vs 69, 60 vs 78, 40 vs 65, 29 vs 57, 33 vs 58). At the 2‐year follow‐up, 236 patients (82%) reported they were satisfied with the outcome of surgery. We conclude that arthroscopic treatment for FAI resulted in statistically and clinically significant improvements in outcome parameters.